Incorporating 4D into Bioprinting: Real-Time Magnetically Directed Collagen Fiber Alignment for Generating Complex Multilayered Tissues - Cristian, Catalin; Lin, Ying-Ying; Blaeser, Andreas; Schoeneberg, Jan; Vogt, Michael; Buhl, Eva Miriam; Fischer, Horst; Campos, Daniela Filipa Duarte; Betsch, Marcel (Advanced Healthcare Materials, 2018)
In vitro multilayered tissues with mimetic architectures resembling native tissues are valuable tools for application in medical research. In this study, an advanced bioprinting strategy is presented for aligning collagen fibers contained in functional bioinks. Streptavidin-coated iron nanoparticles are embedded in printable bioinks with varying concentrations of low gelling temperature agarose and type I collagen. By applying a straightforward magnetic-based mechanism in hydrogels during bioprinting, it is possible to align collagen fibers in less concentrated hydrogel blends with a maximum agarose concentration of 0.5 w/v%. Conversely, more elevated concentrations of agarose in printable blends show random collagen fiber distribution. Interestingly, hydrogel blends with unidirectionally aligned collagen fibers show significantly higher compression moduli compared to hydrogel blends including random fibers. Considering its application in the field of cartilage tissue engineering, bioprinted constructs with alternating layers of aligned and random fibers are fabricated. After 21 days of culture, cell-loaded constructs with alternating layers of aligned and random fibers express markedly more collagen II in comparison to solely randomly oriented fiber constructs. These encouraging results translate the importance of the structure and architecture of bioinks used in bioprinting in light of their use for tissue engineering and personalized medical applications.
CRIS-Team Scopus Importer:2022-07-20
Keywords: 4D; bioprinting; collagen fiber alignment; magnetic fields; tissue models